2003
DOI: 10.1002/uog.88
|View full text |Cite
|
Sign up to set email alerts
|

Altered fetal circulation in type‐1 diabetic pregnancies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
2
16
1
1
Order By: Relevance
“…Increased peak velocities in the aorta and pulmonary arteries in fetuses of diabetic mothers compared with normal values have been reported (Rizzo et al, 1992). Although fetuses of diabetic pregnancies may have an accelerated increase in maximum and mean temporal velocities across the atrioventricular valves relative to normal pregnancies (Lisowski et al, 2003), interpretation of valve flow velocity patterns and ventricular performance via echocardiography has some limitations, as these parameters are affected by heart rate, afterload, preload, and ventricular compliance. In normal pregnancies and those with pregestational diabetes, there is a progressive decrease in placental vascular resistance with gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased peak velocities in the aorta and pulmonary arteries in fetuses of diabetic mothers compared with normal values have been reported (Rizzo et al, 1992). Although fetuses of diabetic pregnancies may have an accelerated increase in maximum and mean temporal velocities across the atrioventricular valves relative to normal pregnancies (Lisowski et al, 2003), interpretation of valve flow velocity patterns and ventricular performance via echocardiography has some limitations, as these parameters are affected by heart rate, afterload, preload, and ventricular compliance. In normal pregnancies and those with pregestational diabetes, there is a progressive decrease in placental vascular resistance with gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Fetuses of diabetic pregnancies have been shown to have an accelerated increase in maximum and mean temporal velocities across atrioventricular valves through gestation relative to normal pregnancies. 9 Increased left and right ventricular outputs adjusted for fetal weight have also been observed. 9 Lower right atrioventricular valve inflow E (early diastole)/A (atrial systole) velocity ratios have been demonstrated, particularly later in gestation.…”
Section: Evolution Of Fetal Myocardial Changes In Maternal Diabetesmentioning
confidence: 97%
“…9 Increased left and right ventricular outputs adjusted for fetal weight have also been observed. 9 Lower right atrioventricular valve inflow E (early diastole)/A (atrial systole) velocity ratios have been demonstrated, particularly later in gestation. 10 11 Of these parameters, only lowered E/A wave ratio has been shown to be associated with worse maternal glycaemic control, which may be indirectly due to changes in fetal heart rate, ventricular wall thickness and haematocrit.…”
Section: Evolution Of Fetal Myocardial Changes In Maternal Diabetesmentioning
confidence: 97%
“…Increased metabolic demand and relative hypoxia can act as a haemodynamic stimulant and significantly increase cardiac output. 22 In addition, corticosteroids can have a direct anabolic effect on myocardium, 2 cause systemic hypertension, and increase the afterload. 13 This type of hemodynamic stimulant, hyperinsulinaemia and or iatrogenic corticosteroids, can cause neonatal cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%